Anti-Russian Sanctions: Structure and Strategies of Counter-Action - M. V. Rukinov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
The paper contains an analysis of the structure of the anti-Russian sanctions from the point of view of their goals and tools that are used. It is demonstrated that the sanctions aim at the limitation of capital inflow into Russia and at countering technological development of our country. The policy of substitution of import as an anti-sanction tool is analyzed. It is demonstrated that this policy is limited. Recommendations for the complex anti-sanction strategy are formulated.